2017
DOI: 10.1186/s12929-016-0314-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sarcosine and N, N-dimethylglycine on NMDA receptor-mediated excitatory field potentials

Abstract: BackgroundSarcosine, a glycine transporter type 1 inhibitor and an N-methyl-D-aspartate (NMDA) receptor co-agonist at the glycine binding site, potentiates NMDA receptor function. Structurally similar to sarcosine, N,N-dimethylglycine (DMG) is also N-methyl glycine-derivative amino acid and commonly used as a dietary supplement. The present study compared the effects of sarcosine and DMG on NMDA receptor-mediated excitatory field potentials (EFPs) in mouse medial prefrontal cortex brain slices using a multi-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
8
0
2
Order By: Relevance
“…DMG is a partial agonist at the glycine binding site of NMDA receptors. However, although DMG alone did not alter the NMDA receptor-mediated excitatory field potentials, DMG acts as an agonist at the glycine binding site of NMDA receptors in combination with glutamate [ 62 ]. Therefore, the agonist effect of DMG on NMDAR can be decreased with decreased medial prefrontal glutamate–glutamine concentration, and decreased NMDAR expression has been reported to occur during chronic administration of oxytocin [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMG is a partial agonist at the glycine binding site of NMDA receptors. However, although DMG alone did not alter the NMDA receptor-mediated excitatory field potentials, DMG acts as an agonist at the glycine binding site of NMDA receptors in combination with glutamate [ 62 ]. Therefore, the agonist effect of DMG on NMDAR can be decreased with decreased medial prefrontal glutamate–glutamine concentration, and decreased NMDAR expression has been reported to occur during chronic administration of oxytocin [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in our previous study [ 11 ], the behavioral effects of oxytocin can be observed at a maximum of 2 weeks, with deterioration at 4 weeks, in a 6-week treatment period. Taken together, these findings suggest that in the acute phase (e.g., 0–2 weeks), increases in DMG induced with oxytocin administration can act as a partial agonist at the glycine binding site of NMDAR with glutamate [ 62 ]. In addition, administered oxytocin has clinical effects during the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcosine (1), currently used as a dietary supplement and as a non-specific glycine transport inhibitor, also holds promise as an adjuvant therapy with sodium benzoate for the treatment of schizophrenia (Lin et al, 2017) and depression, as recently discussed in a review (Mathew, 2013). N, , which is also used as a dietary supplement, reportedly improves immune responses, acts as an athletic performance enhancer, displays anticonvulsant activity and may have use as an antidepressant in patients with autism (Lee et al, 2017). According to a recent review by Wilcken, glycine betaine (3) is used pharmaceutically in anhydrous form as Cystadane®, an adjunctive treatment for homocystinuria and can offer numerous other benefits to human health such as attenuation of liver injury (Wilcken, 2017).…”
Section: The Occurrence Of N-alkyl-α-amino Acidsmentioning
confidence: 99%
“…In the glutamate hypothesis of schizophrenia, abnormal glutamate uptake by glial cells can result in decreased N-methyl-D-aspartate (NMDA) receptor function [1,[3][4][5][6][7]. Dysfunction of NMDA receptors results in the disruption of downstream dopamine signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of the NMDA receptor via allosteric binding of glycine can enhance glutamate binding [1,[3][4]. Sarcosine (N-methyl glycine) is a type 1 glycine transporter inhibitor (GlyT1), that increases the synaptic concentration of glycine by preventing its reuptake by glial cells.…”
Section: Introductionmentioning
confidence: 99%